Pengenalan Alat Tangkap Bubu Terhadap Anak-Anak di Desa Cot Suruy Kecamatan Ingin Jaya Kabupaten Aceh Besar - Thaib, Azwar; Nurhayati; Syahputra, Faisal; Naufal, Agus; Amonda, Roy (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
Fish trap is one of the fishing tools that is often used at night. This fishing gear is used in irrigation or swamps. The purpose of this activity is to provide education to participants about traditional fishing gear to foster awareness in protecting the environment. Community service activities were carried out in Cot Suruy village, Ingin Jaya District, Aceh Besar Regency. This service activity was attended by 10 participants who were dominated by children. This activity was carried out in three stages, including socialization and counseling, demonstrations of the practice of using bubu fishing gear, discussion and evaluation. The results of this service activity can be concluded that this activity has a positive impact on the participants, in this case they care about the environment and are ready to preserve local wisdom.